Free vibration and chatter stability of a rotating thin-walled composite bar. (September 2018) - Ma, Jingmin; Ren, Yongsheng
The free vibration and chatter stability of a rotating thin-walled composite bar under the action of regenerative milling force were investigated in this article. The free vibration equations of the rotating thin-walled composite bar were presented and solved by the Galerkin method according to the derived Lagrange equation for the rotating thin-walled composite bar, and the influences of the taper ratio, ply angle, and mode number on the first natural frequency were analyzed. In order to study the chatter stability of the rotating thin-walled composite bar, the time-delay motion equation of the system was derived with consideration of the effects of regenerative milling force and internal/external damping. The two-mode Galerkin method was used to discretize the time-delay free vibration equations, and the semi-discrete method in the time domain was employed to predict the stability lobes. Finally, the correctness of the method was validated, and the stability analysis of the rotating thin-walled composite bar was conducted. Emphatically, the influences of the ply angle, taper ratio, and internal/external damping on the chatter stability of the rotating thin-walled composite bar were analyzed.